Denitrification along the Stream‐Riparian Continuum in Restored and Unrestored Agricultural Streams. Issue 5 (1st September 2017) - Welsh, Molly K.; McMillan, Sara K.; Vidon, Philippe G.
Abstract : Although floodplain restoration may improve stream‐riparian connectivity and increase channel stability through cross‐vane installation, stream bank regrading, and buffer revegetation, the impact of these geomorphic alterations on denitrification across the aquatic‐terrestrial interface is poorly understood. Seasonal denitrification enzyme activity (DEA) was compared in stream‐riparian ecotones of four streams with varying hydrologic connection, riparian vegetation composition, and agricultural influence. Riparian and stream DEA was generally higher in sites adjacent to agricultural fields due to proximity to nitrate source. Mean DEA was higher in the dormant season (riparian: 928 ± 116 ng N g −1 dry mass [DM] h −1, stream: 108 ± 149 ng N g −1 DM h −1 ) than in the growing season (riparian: 355 ± 55 ng N g −1 DM h −1, stream: 45 ± 40 ng N g −1 DM h −1 ) and was influenced by antecedent precipitation, soil texture, and landscape characteristics (land use, vegetation type, topography) in multivariate models. Hot spots of denitrification occurred at the confluence of fine soil textures with high organic matter and moisture, often at low‐lying areas of the landscape. At the restored site, we observed enhanced denitrification in the reconnected floodplain but decreased stream denitrification capacity in pools. Across all sites, streams had lower DEA than riparian zones, stressing the importance of restoration approaches designed to conserve riparian areas and maintain hydrologic connectivity. Easily obtainable data including precipitation, adjacent land use, vegetation, and stream and floodplain geomorphology reasonably predicted denitrification potential compared with more complex models, showing potential for application in water resources and nitrogen management. Core Ideas: Denitrification enzyme activity (DEA) was measured in agricultural stream ecotones. Restoration led to sediment coarsening and reduced denitrification in stream pools. Denitrification hot spots occurred in saturated, reconnected near‐stream zones. Land use and geomorphology are important field predictors of denitrification. Riparian slope, bank height, and vegetation type can inform nitrogen management.